Sistema de gestión documental y satisfacción de los trabajadores de la Municipalidad Provincial de Putumayo 2022 - Saenz Jipa, Jonathan (2024)
The recent study entitled: Document management system and satisfaction of the workers of the Provincial Municipality of Putumayo, had as general: Determine the relationship between the use of the document management system and the satisfaction of internal users of the Provincial Municipality of Putumayo. The type of research is fundamental, with non-experimental design and it was carried out with a population of 53 internal users. Coming to the conclusion that there is a relationship between both variables, therefore, it is determined that it is crucial that they automate the institution's documentation system, thus helping employees to fulfill their duties with ease, because they will have a better organization. , the files will be kept in a manner that prevents damage and waiting times are shortened, so that they would work in a more pleasant and orderly environment, which is why they are sought to collaborate and subsequently grow appropriately to achieve the objectives of the Municipality under study.